Resilience, spiritual well-being, and self-esteem among students with disabilities in Jordan: A cross-sectional study - Mutaz Fuad Alradaydeh; Mohammad A. Al-Ma’ani; Omar I. Alorani; Mohammad Othman Abudari (Belitung Nursing Journal, 2026)
Background: University students with hearing, visual, and motor disabilities report several challenges that is negatively associated with psychological wellbeing. Although the numbers of students with disabilities in higher education is continuously increasing, the nursing related studies about the association of resilience, spiritual well-being, and self-esteem remains limited. Objectives: This study examined the associations among resilience, spiritual well-being, and self-esteem among university students with disabilities. Methods: A cross-sectional correlational design was used. University students with visual, hearing, and motor disabilities in Jordan were recruited through convenience sampling between February and April 2025. Data were collected using an electronic survey that included a demographic questionnaire, the Connor–Davidson Resilience Scale, the Functional Assessment of Chronic Illness Therapy–Spiritual Well-Being Scale, and the Rosenberg Self-Esteem Scale. Data were analyzed using descriptive statistics, one-way ANOVA, and Pearson’s correlation. Findings: A total of 110 students participated (mean age = 22.7 years, SD = 4.18); 43.6% had visual disabilities, 36.4% had hearing disabilities, and 20.0% had motor disabilities. The mean resilience score was 71.29 (SD = 17.40) out of 100, the mean spiritual well-being score was 36.30 (SD = 7.12) out of 48, and the mean self-esteem score was 29.60 (SD = 4.79) out of 40. Students with visual disabilities reported significantly higher levels of spiritual well-being (F = 6.09, p = 0.003) and self-esteem (F = 23.26, p < 0.001). Lower self-esteem levels were observed among first-year students (F = 5.39, p = 0.002). Significant positive correlations were found between resilience and spiritual well-being (r = 0.698, p ≤ 0.01), resilience and self-esteem (r = 0.579, p ≤ 0.01), and spiritual well-being with self-esteem (r = 0.602, p ≤ 0.01). Conclusions: The significant positive associations among resilience, spiritual well-being, and self-esteem emphasizing the prompt need for psychological support across different type of disabilities. Continuous nursing assessment and psycho-social intervention for students with disabilities should be considered in the university health programs.